Literasi Keuangan Digital Peer-To-Peer (P2P) Lending Kepada Pelaku UMKM Di Sendangmulyo Semarang - Lestari, Rohmini Indah; Arifin, Zaenal; Sudarmanto, Kukuh (Universitas Islam Nahdlatul Ulama Jepara, 2022)
People started looking for information about Fintech Peer-To-Peer (P2P). Online loans have become attached a negative stigma; on the other hand, online credit platforms are very much needed by the community. Through the Financial Services Authority, the government uses this momentum to carry out digital financial literacy regarding online credit. In line with the government's goals, the purpose of Community Service activities from the Master of Law Study Program Universitas Semarang (USM) is to increase understanding, insight, and financial knowledge about Fintech P2P Lending to MSME Groups in Sendangmulyo Village, Semarang City. The material provided includes the development of Fintech P2P Lending in Indonesia. Second, explain the benefits and risks and how to choose an online loan platform registered and licensed at the OJK. Third, explain the consequences and legal protection for ordinary people so they do not worry when facing legal problems with illegal online credit companies. Fourth is the existence of an Investment Alert Task Force (SWI), which was formed to prevent and handle alleged unlawful acts by illegal online loan companies. This activity hopes that the community and MSME actors can choose a legal online credit platform and avoid the entanglement of illegal online credit.Â Masyarakat mulai mencari informasi mengenai Fintech Peer-To-Peer (P2P) Lending atau pinjaman online menjadi dikenal masyarakat setelah muncul berita maraknya jeratan pinjaman online ilegal. Pinjaman online menjadi lekat dengan stigma negatif, di sisi lain platform pinjaman online sangat dibutuhkan oleh masyarakat. Selaras dengan tujuan pemerintah maka tujuan dari kegiatan Pengabdian Kepada Masyarakat (PKM) adalah meningkatkan pemahaman, wawasan, pengetahuan keuangan digital mengenai Fintech P2P Lending kepada Kelompok UMKM di Kelurahan Sendangmulyo Kota Semarang. Materi yang diberikan meliputi perkembangan Fintech P2P Lending di Indonesia. Kedua, menjelaskan manfaat serta risiko serta bagaimana memilih platform pinjaman online yang terdaftar dan berijin di OJK. Ketiga, memberi penjelasan konsekuensi dan perlindungan hukum bagi masyarakat awam agar tidak khawatir saat menghadapi masalah hukum dengan perusahaan pinjaman online ilegal. Keempat, keberadaan Satuan Tugas Waspada Investasi (SWI) yang dibentuk pemerintah dalam rangka pencegahan dan penanganan dugaan tindakan melawan hukum oleh perusahaan pinjaman online ilegal. Harapan dari kegiatan ini adalah agar masyarakat dan pelaku UMKM dapat memilih platform pinjaman online yang legal serta terhindar dari jeratan pinjaman online ilegal.